Etične dileme v zdravstvenem zavodu z vzgojno-varstveno dejavnostjo - Karapandža, Jurij (Rehabilitacija (Ljubljana), 2017)
In this article, ethical questions arising in the care for severly brain-injured children treated in our institutinon for long-term care and special education are discussed. As noted elsewhere in literature, the decisions about treatment for such children give rise to some of the most challenging ethical dilemmas in pediatrics. The questions whether or not certain types of treatment are in the best interest of the child, whether they improve quality of life or just prolong life and whether the parents are permitted to request that a particular treatment be provided for their child are crucial for the debate. Based on the official ethical recommedatins, the presented studies and our experience, we strongly support and practise a shared decision-making approach.
Keywords: disabled child; ethical issues; Ethics; etične dileme; etika; long-term care institution; otrok s posebnimi potrebami; special education; specialna pedagogika; vzgojnovarstveni zavodi